A EXPERIÊNCIA DE UM GRUPO DE PROFESSORES ENVOLVENDO ENSINO DE QUÍMICA E INFORMÁTICA - Gabini, Wanderlei Sebastião [UNESP]; Diniz, Renato Eugênio Da Silva [UNESP] (Faculdade de Educação da Universidade Federal de Minas Gerais, 2007)
The main goal of this work was to investigate the insertion of Information and Communication Technologies (ICT) as strategy for the Chemistry teaching. During the meetings of a teachers' group of this discipline, had been discussed some subjects as the experiences already lived by them about this subject, the analysis and exploration of softwares, besides the elaboration and application of a proposal of class in the Computer lab of the schools where they acted. It was evident, in this study, the importance of a space where the professor can discuss its practical professional, to plan available didactic actions and to know softwares, as well as the fact of Information and Communication Technologies (ICT) being a viable resource in the education of Chemistry.

Este trabalho teve como objetivo investigar a inserção da informática como estratégia didática para o ensino de Química. Por meio de encontros de um grupo de professores dessa disciplina, foram discutidas experiências já vivenciadas por eles sobre este tema, análise e exploração de softwares, além da elaboração e aplicação de uma proposta de aula na Sala Ambiente de Informática das escolas em que atuavam. Ficou evidente, nesse estudo, a importância de um espaço para o professor discutir sua prática profissional, planejar ações didáticas e conhecer os softwares disponíveis, bem como o fato de a informática ser um recurso viável no ensino de Química.
The experience of a group of teachers involving Chemistry teaching and Information and Communication Technologies (ICT)
Keywords: chemistry teaching; information and communication technologies (ict); teacher education; ensino de química; informática; formação de professores